FMCW Interference Waveform Estimation Based on Intentional Local Interference for Automotive Radars - Sungpil Cheon; Hyungwoo Kim; Byungkwan Kim (Journal of Electromagnetic Engineering and Science)
We propose a new method to estimate the waveforms of frequency-modulated continuous-wave (FMCW) interferers by intentional interference. The proposed method utilizes the crossing interference of FMCW radar by adaptive waveform configuration. The victim radar analyzes the periodicity and frequency of the interference signal from the mixer at the FMCW receiver. The bandwidth, slope, and intervals of the interferer waveform are derived from multiple adaptive waveforms from interference detection results. The estimated time and frequency waveform parameters of the interferer can be utilized to generate an interference-free waveform. The proposed approach has been tested and validated using two different mmWave commercial off-the-shelf automotive FMCW radars: the AWR2243 and AWR2944 evaluation boards. In three different scenarios in indoor and outdoor environments, the proposed method successfully estimated interferer waveform parameters with 0.9 seconds of monitoring processing and less than 3% error.